Sexual violence on trial: local and comparative perspectives - Killean, Rachel; Dowds, Eithne; McAlinden, Anne-Marie (Routledge studies in crime and society, 2021)
Foreword Part I: The Criminal Justice Process 1 Sexual Offence Trials in Northern Ireland: The Cultural and Legal Dimensions Rachel Killean, Eithne Dowds and Anne-Marie McAlinden 2 Reflections on Practice: Experiences of Providing Care to Victims in the Rowan Sexual Assault Referral Centre in Northern Ireland Gail Jackson 3 Sexual Crime -- A Policing Perspective Zoe McKee 4 Serious Sex Offences in England and Wales: Defending the Indefensible Jeremy Dein and Luke Marsh 5 Supporting Victims through the Trial Process Geraldine Hanna 6 Sexual Offence Trials: The Practical Challenges for a Judge Tasked to Deliver Justice. Judge Patricia Smyth Part II: Social and Cultural Influences 7 Asking for It: How Rape Myths Can Prejudice Trials and Potential Solutions Rosie Cowan 8 Forced to Penetrate Cases: Deconstructing Myths and Stereotypes Siobhan Weare 9 Harmful Sexual Behaviours Among Children and Young People On-Line: Cultural and Regulatory Challenges Elizabeth Agnew and Anne-Marie McAlinden 10 Exploring Intimate Partner Sexual Violence: A Practitioners Perspective Sonya McMullan 11 A Hierarchy of Masculinity and Sexuality: Gendering the Police, and the Obfuscation of Policing Sexual Violence Against Non-Heterosexual Victims Aliraza Javaid Part III: Comparative Perspective 12 Regulation of Media and Social Media Comment on Rape Trials: Achieving Best Practice Susan Leahy 13 Rethinking Affirmative Approaches to Consent: A Step in the Right Direction Eithne Dowds 14 Legal Representation for Sexual Assault Complainants Rachel Killean 15 Restorative Justice after Sexual Violence: An International Perspective Marie Keenan 16 Challenges in the Investigation and Prosecution of Rape and Serious Sexual Offences in Scotland Michele Burman and Sandy Brindley Part IV: Alternative Perspectives and Future Reforms 17 Contextualising Violence: An Anti-Carceral Feminist Perspective Gillian McNaull 18 Breaking the Silence to End the Violence: 'Speaking Out' as Feminist Strategy Tanya Serisier 19 Cultural Scaffolding and the Long View of Rape Trials Olivia Smith 20 Putting Sexual Violence on Trial: Challenges and Future Directions Eithne Dowds, Anne-Marie McAlinden and Rachel Killean Index